Authoritarianism Beyond Disposition: A Literature Review of Research on Contextual Antecedents - Schnelle, Caroline; Baier, Dirk; Hadjar, Andreas; Boehnke, Klaus (Frontiers in Psychology, 2021)
A core debate in authoritarianism research relates to the stability of authoritarianism, i.e., whether it is a dispositional phenomenon socialized in early childhood or even genetically predisposed, or whether it is impacted by time-sensitive, exterior conditions. Whereas certain individual authoritarian tendencies emerge as a rather stable personality trait, there is also empirical evidence for a dynamic influence of external factors. This review article provides a conceptual multilevel framework for the study of authoritarianism and offers an insight into the state-of-research on socialization and situational influences, with a particular focus on threat. Findings are discussed with regard to key theories of authoritarianism.